The home that was our country : a memoir of Syria - Malek, Alia, 1974- (New York, NY : Nation Books, an imprint of Perseus Books, LLC, a subsidiary of Hachette Book Group, Inc., 2017)
In The Home that Was My Country, Syrian-American journalist Alia Malek chronicles her return to her family home in Damascus and the history of the Jabban apartment building. Here, generations of Christians, Jews, Muslims, and Armenians lived, worked, loved, and suffered in close quarters. In telling the story of her family over the course of the last century, Alia brings to light the triumphs and failures that have led Syria to where it is today. Her book bristles with insights, as Alia weaves acute political analysis into intimate scenes, interlacing the personal and the political with subtlety and grace. After being in and out of Syria growing up, Alia came back to Syria as a journalist at the time of the Arab Spring, striving to understand it as the country was beginning to disintegrate. As days go on, Alia learns how to speak the language that exists in a dictatorship, while privately confronting her own fears about her country's future, and learns how to carry on with everyday life. This intimate portrait of contemporary Syria will shed more light on its history, society, and politics than all of today's war reporting accounts written from the Syrian front. It makes for an eye-opening, highly moving, and beautiful read, and finds the humanity behind the disastrous daily headlines.
Prologue : leaving -- Generations -- Origins -- Sheika -- Adrift -- Pack your bags and go -- Locked in -- Locked out -- A wedding in hama -- No man's land -- They did it to themselves -- In the eye of the belly -- Return -- Tahrir squares -- Psychodrame -- Fatherland -- In the cards -- Routine -- Suspicion -- Unraveling -- Power -- Displaced -- Gone -- Epilogue: bound.
Keywords: Malek, Alia, -- 1974- -- Family; Damascus (Syria) -- Biography; Damascus (Syria) -- History; Syria -- History; Biographies